Determinants in Choosing a Career as an Accountant in the Government or Non-Government Sector - Putri, Dwi; Mulyani, Sri - (Universitas Padjadjaran, 2024)
Governments and companies rely on expert and skilled accountants to prepare reliable and relevant financial and management reports. As a result, pursuing a career as an accountant in the government or non-government sector is a viable option for graduates of accounting programs. This study aims to identify the factors that influence students and graduates of the Bachelor of Accounting program to pursue careers as accountants in government or non-government sectors. Qualitative research methods were used to collect data through interviews with 67 students from UNPAD and UPI, 15 UNPAD and UPI graduates working in the non-government sector, and 15 UNPAD and UPI graduates working in the government sector. Based on the interviews, it was found that job security, work-life balance, financial and non-financial benefits, academic achievement, parental influence, and job market considerations are all factors that students and graduates of the Bachelor of Accounting program weigh when considering a career as a government or non-government accountant. Gender was found only to influence students and graduates who work in the government sector. Additionally, prestige was another factor that was considered by interviewees when choosing a career as a government accountant.